Transparansi dan Akuntabilitas Pengelolaan APBDes 2024 di Desa Sowanlor, Jepara - Lestari Widiah Ningsih; Lingga Yuliana (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
. This study aims to analyze the implementation of the principles of transparency and accountability in the management of the Village Revenue and Expenditure Budget (APBDes) in Sowanlor Village, Kedung Sub-district, Jepara Regency, in 2024. The research method used is descriptive qualitative analysis, with a focus on secondary data analysis. The main focus of this research is to assess the extent to which transparency and accountability principles are applied in the planning, implementation, and evaluation phases of the APBDes by the village government. The results indicate that although the village government has made efforts to disseminate financial information and involve the community in budget planning, there are still obstacles related to information openness and public participation. The delivery of financial information is considered insufficiently detailed and not easily understood, while community participation in program monitoring and evaluation remains limited. This study recommends that the village government enhance the quality of financial information disclosure to be more transparent and accessible to the public. Additionally, it is essential to strengthen community involvement in all stages of village budget management, including implementation and evaluation, in order to foster more transparent and accountable village financial governance.